Microwave properties of bitumen modified with waste cooking oil (WCO) - Adamu, Ibrahim Aliyu (2019)
Bitumen is a rheological, viscoelastic, thermoplastic and extremely complex material that has hydrocarbons as its predominant molecules with slight traces of others. Bitumen is semi solid at room temperature, liquid at high temperature and solid at very low temperature. Due to its complexity, till date complete understanding of its properties have not been fully known. Various techniques/methods have been developed by many researchers in order to study the behaviour of this complex material. In this work, we studied the performance of bitumen PEN 60 – 70 and PG 76 modified with Waste Cooking Oil (WCO) using the conventional tests and, Dielectric Constant (DC) and Loss Factor (LF). The conventional tests conducted were penetration, softening point and viscosity tests. The DC measurement was carried out at 2.45 GHz (ISM Band) while the LF was measured at 500 MHz frequencies. The results of the conventional tests show that increasing the percentage of WCO has effect on the bitumen binders by increasing their penetration values and at the same time decreasing their softening point and viscosity. Also based on the DC value, the performance of PG 76 bitumen binder reduced with the increment in the WCO percentage. However, the results of the LF for two modified bitumen binders were illogical. Comparatively, the modified PG 76 bitumen binder will performance better than the modified PEN 60 – 70 bitumen.